The obesity reality : a comprehensive approach to a growing problem - Ali, Naheed, 1981- (Rowman & Littlefield Publishers, 2012)
Although every day we read news reports linking health problems to diet and lifestyle, there remains a dearth of books on the topic that consider obesity from a variety of standpoints that include medical, personal, financial, and related considerations. This book discusses these viewpoints to explain how and why the problem exists both in the United States and around the world, and in men, women, children. More than a billion people are overweight and that number is expected to increase substantially over the next decade. How can we live past 90 while being obese? How can we remain healthy until our last breath? During the last decade, doctors have been successfully applying medical principles to the search for an obesity cure. But there is no magic medication, no vaccine that can head off the obesity epidemic as sweeps across the planet. The author discusses the realities of obesity and its repercussions, which include poor health, high medical costs, restrictions on lifestyle and activities, and more. He shows how we can address obesity, starting in childhood, to prevent it from getting worse, both on a personal and on a societal level, and how we can reverse its effects through proper diet, exercise, and lifestyle choices as well as medical procedures and medications.